Implikasi Ketiadaan Sanksi terhadap Ketentuan Keterwakilan 30% Perempuan dalam Daftar Calon Legislatif di Indonesia - Ach. Muzayyin (Jurnal Hukum Lex Generalis, 2024)
Women's representation in politics is part of an affirmative policy aimed at achieving gender equality in Indonesia. Related regulations, such as Law  Number 7 of 2017 concerning Elections and KPU Regulation Number 10 of 2023, require political parties to include at least 30% women in the list of legislative candidates. However, the absence of sanctions against political parties that do not meet this provision is a major obstacle in its implementation. As a result, many political parties only comply with the rules administratively without providing substantive opportunities for women to contribute to politics. This study uses a normative-juridical method with a legislative and conceptual approach to analyze the weaknesses of women's representation regulations. The results show that the absence of sanctions results in weak effectiveness of affirmative policies, limited representation of women in legislative institutions, and reduced accountability of political parties in supporting gender equality. Although there has been an increase in the number of women running for office, the number of those who are successfully elected remains far from ideal. To increase the effectiveness of women's representation policies, a revision of regulations is needed by setting strict sanctions for violators, accompanied by consistent supervision. This step is expected to create a more inclusive political system, support substantive representation of women, and strengthen the principles of just democracy in Indonesia.